Geomorphosite Assessment in the Proposed Geopark Vistula River Gap (E Poland) - Warowna, Justyna; Zgłobicki, Wojciech; Gajek, Grzegorz; Telecka, Małgorzata; Kołodyńska-Gawrysiak, Renata; Zieliński, Paweł (Quaestiones Geographicae, 2014)
Geomorphosites are among major assets for the development of geotourism. An accurate assessment of spatial distribution of their scientific, educational and economic characteristics provides the basis for appropriate design and management of proposed geoparks. Although the problem of assessing their value for geotourism has been discussed by numerous authors, consistent methodology for the assessment of geomorphosites has not been devised so far. In the present study, we conducted a geotourist evaluation of geomorphosites located within the proposed geopark Vistula River Gap. We assessed a total of 76 sites using 18 assessment criteria. The results indicate not uniform spatial distribution of sites having the highest value. The application of cluster analysis to evaluation results enabled us to distinguish groups of sites with similar characteristics and thus to identify groups of geomorphosites in relation to which various measures should be taken in order to increase the possibilities of their tourist use.